Dysregulated type I/III interferon system in circulation from patients with anti-MDA5-positive dermatomyositis - Akira Yoshida; Takahisa Gono; Yuka Okazaki; Masumi Shimizu; Yutaka Igarashi; Yoshihiro Kitahara; Tomoyuki Fujisawa; Takafumi Suda; Shoji Yokobori; Rimpei Morita; Masataka Kuwana (Scientific Reports)
Abstract Anti-melanoma differentiation-associated gene 5 (MDA5)-positive dermatomyositis (DM) is often complicated by rapidly progressive interstitial lung disease (RP-ILD), leading to early mortality. Previous studies on the pathogenesis of anti-MDA5-positive DM highlighted type I interferons (IFNs), while recent investigations reported the significance of a type III IFN, IFN-λ3. We investigated a range of cytokines, including type I/II/III IFNs, in serum samples from anti-MDA5-positive DM patients collected at diagnosis before treatment introduction. Elevations of IFN-β and λ3 were identified as the hallmark of anti-MDA5-positive DM, in comparison with other myositis subtypes, systemic lupus erythematosus, and COVID-19 pneumonia. The elevation of IFN-λ3 was associated with decreased CD56dimCD16pos NK cells in circulation. The unique cytokine profile with type I/III IFN upregulation in anti-MDA5-positive DM was replicated in independent validation cohorts. A cluster analysis using serum type I/III IFN levels identified three subgroups in anti-MDA5-positive DM: mild elevations of IFN-α/β and λ3; a marked increase in IFN-λ3 alone; and pronounced elevations of IFN-α/β with mild to moderate increase in IFN-λ3. Patients in the cluster with a marked elevation of IFN-λ3 alone tended to present with RP-ILD and decreased survival. The combination of serum type I/III IFN levels could serve as a prognostic biomarker in anti-MDA5-positive DM.